Enhanced photocatalytic activity of perovskite NaNbO3 by oxygen vacancy engineering. Issue 22 (28th May 2019) - Yang, Bian; Bian, Jihong; Wang, Lei; Wang, Jianwei; Du, Yaping; Wang, Zhiguang; Wu, Chao; Yang, Yaodong
Abstract : Oxygen vacancy engineering can improve the photocatalytic activity of perovskite NaNbO3 . Abstract : NaNbO3 with oxygen vacancies has been successfully synthesized through a well controllable solid-state reaction, whose photocatalytic performances have been prominently enhanced by almost 2.4 times compared with just annealed NaNbO3 (the control sample). When oxygen vacancies were introduced into the perovskite, the color of NaNbO3 turned black and the band gap was decreased, resulting in its remarkable absorption under visible light, and its higher symmetry also favors the electron transfer. More importantly, oxygen vacancies lead to larger specific surface area and higher charge density, which play non-negligible roles in improving the visible-light-activities. These encouraging findings prove that oxygen vacancy engineering is a feasible and general strategy to improve the photocatalytic performances of perovskite oxides, which will promote many related applications.